Seaweed resources of Argentina (S W Atlantic): production, bio-ecological, applied research and challenges for sustainable development - María Paula Raffo; Fernando Dellatorre; Marina Ciancia (Applied Phycology, 2022)
Argentina comprises more than 5000 km of coastline with a considerable diversity of seaweeds, some of which have the potential to be transformed into fishery resources. However, when compared with other marine resources, the exploitation of the seaweed species in terms of the harvesting methods, their sustainability and available information on biological and ecological features, as well as their potential applications, is scarce or outdated. In this context, this review includes an integrated analysis of production statistics of selected seaweeds in Argentina. In addition, an extensive revision of taxonomic, bio-ecological, environmental and applied issues involving Argentinean seaweed resources is provided. Furthermore, we include novel information about the changes in resource availability which occurred during the last 20 years and their consequent impacts on the seaweed industry. The Argentinean seaweed industry developed raw materials biomass production in the 1960s and extraction of phycocolloids in the 1970s which dropped to very low levels to the present. Information here presented contributes directly to the UN SDG Goal 14: Life below water, providing a theoretical framework to understand how and which of the global change drivers affect sustainability of marine resources. Additionally, a detailed review is presented on phycocolloids from Argentinean seaweed resources. Actions are proposed that would contribute to the enhanced sustainable development in Argentina. The review suggests that reactivation of an Argentinean seaweed industry requires an update of legal frameworks, regarding exploitation of Argentinean seaweeds together with the necessary developments of science and industry.